2023
DOI: 10.3390/jpm13071038
|View full text |Cite
|
Sign up to set email alerts
|

Current Cardioprotective Strategies for the Prevention of Radiation-Induced Cardiotoxicity in Left-Sided Breast Cancer Patients

Vasiliki Nikovia,
Evangelos Chinis,
Areti Gkantaifi
et al.

Abstract: Background: Breast cancer (BC) is the most common malignancy in females, accounting for the majority of cancer-related deaths worldwide. There is well-established understanding about the effective role of radiotherapy (RT) in BC therapeutic strategies, offering a better local–regional control, prolonged survival, and improved quality of life for patients. However, it has been proven that conventional RT modalities, especially in left-sided BC cases, are unable to avoid the administration of high RT doses to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The female patients could be divided in different categories on the basis of the target volume. Further research is required to evaluate whether previously reported cardioprotective strategies [41] related to prone positioning, gating and proton therapy may have a considerable impact on LAD and LV exposure. It should also be mentioned that a follow-up study of patients irradiated for left-sided breast cancer, including the appropriate heart examinations, could reveal the association of radiation-induced cardiac complications with the dose absorbed by the LAD or LV.…”
Section: Discussionmentioning
confidence: 99%
“…The female patients could be divided in different categories on the basis of the target volume. Further research is required to evaluate whether previously reported cardioprotective strategies [41] related to prone positioning, gating and proton therapy may have a considerable impact on LAD and LV exposure. It should also be mentioned that a follow-up study of patients irradiated for left-sided breast cancer, including the appropriate heart examinations, could reveal the association of radiation-induced cardiac complications with the dose absorbed by the LAD or LV.…”
Section: Discussionmentioning
confidence: 99%